Beginning of historic-legal science in Ukraine (XIX – beginning of XX of century): pre-conditions, features, personalias, periodicals - Homotiyk, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The peculiarities and prerequisites for the development of historical and legal science in connection with the establishment of universities in Ukraine are determined. It is emphasized that for a certain period there is a close connection of historical and legal science with the history of the Ukrainian people and its state. It is analyzed that, for the most part, the first intelligence studies defined the history of Ukrainian law as part of Russian law, observing the principles of a single "all-Russian" origin, without considering the rights of Ukrainians to separate historical development. Therefore, the main tasks of science are separating from the Russian and Polish concept, the “deidealization” of the missionary role of Austria. The role of university centers and scientific societies in the development of historical and legal science is determined through the prism of the analysis of the contribution of individual scientists and the fulfillment of these tasks. For the most part, the first scientific studies were labeled as “West Russian Law”. Universities in Kharkiv, Kiev, Odessa, Lviv, Chernivtsi, numerous scientific societies that emerged during the 70-90s: historical-philological at the Kharkiv, Kiev and Odessa universities, Nestor Chronicle Historical Society, Southwestern Division of the Imperial Russian Geographical Society, Shevchenko Scientific Society in Lviv, Ukrainian Scientific Society in Kiev and others. initiated the development of historical and legal thought. The first Ukrainian scientific schools appeared in the university environment, although university scholars had to balance the pressure from the outside and their own internal academic values and ideals.